Epidemiological Profile of Patients with Colorectal Cancer from a Hospital in Rio Grande do Sul, Brazil - Rohenkohl, Cecilia Albertoni; Pastorello, Julia; Costa, Natália Rodrigues; Zabot, Gilmara Pandolfo; Cassol, Ornella Sari (Journal of Coloproctology, 2021)
Objective The present study describes the epidemiological profile of patients with colorectal cancer (CRC) from the Hospital de Clínicas de Passo Fundo, Passo Fundo, RS, Brazil, between January 1, 2007 and December 31, 2016.Method Retrospective analysis of secondary data of 1,001 patients from the Hospital Cancer Registry.Results Most subjects were Caucasian males, with a mean age of 63.68 years old. The majority of patients had incomplete elementary education and were married. In addition, 44.5% of the patients had a family history of cancer. Most subjects with a positive past or current history of alcohol intake or smoking were male. The diagnosis was mostly based on anatomopathological findings, with a predominance of adenocarcinomas and upper rectum and distal colon localization. Most lesions were in advanced stages, and the liver was the most common site for metastasis. The predominant treatment was surgery with neoadjuvant/adjuvant therapy. After the first treatment, 49.0% of the patients reported complete remission. The survival rate was 78.8% in 10 months.Conclusion The present research analyzed the profile of CRC patients.
Keywords: colorectal cancer; primary prevention; screening; epidemiological profile; socioeconomic factors; public health